Innovation of Business Models in the Digital Economy: A Case Study of Start-up Companies - Ningsih, Rita; Murti, Wahyu (Green Publisher Indonesia, 2024)
This research aims to analyze the impact of digital technology adoption on the business performance of startup companies in Indonesia. Using a random sampling method, five startups were selected as respondents, and data were collected through a questionnaire that has been tested for validity and reliability. The validity test results show that all questionnaire items are valid, with the calculated r value greater than the r table value. The reliability test using Cronbach’s Alpha coefficient produces a value of 0.78, indicating that the research instrument is consistent and can be reused. Descriptive analysis reveals that the majority of startups operate in the fintech, edutech, and healthcare sectors, with most having utilized technologies such as artificial intelligence (AI) and data analytics. The findings indicate that digital technology adoption positively impacts business performance, especially in enhancing operational efficiency and expanding market reach. Startups that maximize the integration of digital platforms experience significant growth in terms of user numbers and revenue. However, challenges such as cyber security, the digital divide, and marketing competition remain major obstacles. This research also emphasizes the importance of government policies in supporting a conducive digital ecosystem so that startups can overcome these hurdles and continue to innovate. With the right strategies and optimal utilization of technology, startups in Indonesia have great potential to grow and contribute significantly to the national digital economy.